Transmission of Proteus syndrome from father to son?. Issue 11 (November 1991) - Goodship, J; Redfearn, A; Milligan, D; Gardner-Medwin, D; Burn, J
Abstract : We present a male infant with cranial hemi-hypertrophy, a lymphangioma, a lipoma, and epidermal naevi. A diagnosis of Proteus syndrome was made. His father had had a large lymphangioma resected from the right side of the face as a child. We propose that Proteus syndrome has been transmitted from father to son.